2009
DOI: 10.1016/j.jmb.2009.05.085
|View full text |Cite
|
Sign up to set email alerts
|

The Folding Trajectory of RNase H Is Dominated by Its Topology and Not Local Stability: A Protein Engineering Study of Variants that Fold via Two-State and Three-State Mechanisms

Abstract: Proteins can sample a variety of partially folded conformations during the transition between the unfolded and native states. Some proteins never significantly populate these high-energy states and fold by an apparently two-state process. Many proteins, however, populate detectable, partially folded forms during the folding process. The role of such intermediates is a matter of considerable debate. A single amino acid change can convert E. coli ribonuclease H from a three-state folder that populates a kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
(50 reference statements)
2
26
0
Order By: Relevance
“…All of the RNase H proteins in our study retain the canonical RNase H fold (16) and fold through a three-state pathway. This is consistent with suggestions that topology, rather than sequence, is likely the determinant of the folding trajectory for this protein (49) and possibly proteins in general (50). In addition, the robust folding of the RNase H ancestors is consistent with evidence indicating that ASR generates proteins of evolutionary significance, unlike consensus proteins, which, despite being likened to ancestral proteins, have been found to fold poorly in some instances (18,51).…”
Section: Discussionsupporting
confidence: 89%
“…All of the RNase H proteins in our study retain the canonical RNase H fold (16) and fold through a three-state pathway. This is consistent with suggestions that topology, rather than sequence, is likely the determinant of the folding trajectory for this protein (49) and possibly proteins in general (50). In addition, the robust folding of the RNase H ancestors is consistent with evidence indicating that ASR generates proteins of evolutionary significance, unlike consensus proteins, which, despite being likened to ancestral proteins, have been found to fold poorly in some instances (18,51).…”
Section: Discussionsupporting
confidence: 89%
“…Potentially, partial unfolding of an obligate intermediate also applies to RNase H1 folding because the two- and three state folding behavior can be manipulated by point mutants yet folding occurs with the same order [126]. For both a three- [127] and four-helix bundle [102], an intermediate with the majority of the native structure forms in microseconds.…”
Section: Non-native Structuresmentioning
confidence: 99%
“…HX pulse-labeling and equilibrium native-state HX experiments monitored by NMR showed that I core comprises a continuous region of the protein between helix A and strand 5 and that β-strands 1, 2, and 3 and helix E acquire protection much later, consistent with mutational analysis (2)(3)(4). Single-molecule and mutational studies indicated that the intermediate is obligatory, on-pathway, and folds first even when I core is not observably populated (6,7).…”
mentioning
confidence: 99%